2010
DOI: 10.1158/1940-6207.capr-09-0130
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Decision of Breast Cancer Patients to Undergo Contralateral Prophylactic Mastectomy

Abstract: Background Increasing numbers of women with breast cancer are electing for contralateral prophylactic mastectomy (CPM) to reduce the risk of developing contralateral breast cancer. The objective of this study was to identify factors that may impact a patient’s decision to undergo CPM. Methods We identified 2504 women with stage 0–III unilateral primary breast cancer who underwent breast surgery at our institution from January 2000 to August 2006 from a prospectively maintained database. We performed logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
105
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(112 citation statements)
references
References 34 publications
5
105
2
Order By: Relevance
“…We recently reported that only 1.3% of patients treated at our institution between 2000 and 2006 underwent genetic testing before surgery; thus, genetic testing is unlikely to have influenced the choice of treatment in this study period. 34 In our previous work genetic testing was associated with utilization of contralateral prophylactic mastectomy, suggesting that increased utilization of genetic testing could potentially impact prevention of future primary lesions. We also recently reported that up to 20% of patients with TNBC have a BRCA mutation; thus, we expect that TNBC patients will increasingly be referred for genetic testing.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We recently reported that only 1.3% of patients treated at our institution between 2000 and 2006 underwent genetic testing before surgery; thus, genetic testing is unlikely to have influenced the choice of treatment in this study period. 34 In our previous work genetic testing was associated with utilization of contralateral prophylactic mastectomy, suggesting that increased utilization of genetic testing could potentially impact prevention of future primary lesions. We also recently reported that up to 20% of patients with TNBC have a BRCA mutation; thus, we expect that TNBC patients will increasingly be referred for genetic testing.…”
Section: Discussionmentioning
confidence: 95%
“…In general, fewer than 10% of breast cancer patients at our institution undergo breast MRI, and this modality is generally reserved for screening in high risk patients (e.g., lifetime breast cancer risk >20%; genetic predisposition such as BRCA1/2 mutation; prior breast irradiation). 34 …”
Section: Discussionmentioning
confidence: 99%
“…2,1318 More recent research has shown that surgeon recommendation against CPM powerfully reduces receipt. But only about a one third of patients who consider CPM report that their surgeon recommended against it and one third reported no substantial discussion with their surgeon about it.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 To reduce CBC risk, an increasing number of women with DCIS are electing to undergo contralateral prophylactic mastectomy (CPM). 1, 2,4 …”
Section: Introductionmentioning
confidence: 99%